Verlustverrechnung bei Personengesellschaften und anderen transparent besteuerten Gesellschaftsformen Eine rechtsvergleichende Analyse zwischen Deutschland, Frankreich und den USA - Glenk, Caroline (Steuerwissenschaftliche Schriften, 2022)
The thesis deals with the fundamental tax policy question on the "correct" treatment of losses in partnerships and other tax-transparent entities. It is based on a legal comparison with countries in which the borderline between transparent and non-transparent taxation is drawn differently than in Germany (despite similar principles of company law) and in some cases very far-reaching option rights exist. The book deals in a differentiated manner with the "tech-niques" of dealing with corporate losses in corporations and partnerships as well as with the possibilities of an option for the non-transparent or transparent taxation, and culminates in a legislative proposal.